PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI) - Anggi Syuhada; Yusnaini Yusnaini; Eka Meirawati (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
This study aimed at testing and finding the influence of good corporate governance and profitability to tax avoidance. This study used secondary data from financial and annual report of mining companies registered in Indonesian Stock Exchange 2013 -2017. Purposive sampling method was used in this study. Total sample were 55 from eleven companies. Analysis methods applied in this study were both descriptive analysis and statistical analysis technique. The result of the test showed that good corporate governance which was represented by the institutional possession, independent commissionaire council, and audit committee was not significantly influenced to the tax avoidance. Meanwhile profitability was found influenced to the tax avoidance negatively.